2018
DOI: 10.3390/met8070539
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Compression Ratios on Sound Absorption Performance of Porous Nickel–Iron Alloy

Abstract: Abstract:The improvement of sound absorption performance of porous metal is a focus of research in the field of noise reduction. Influences of compression ratios on sound absorption performance of a porous nickel-iron (Ni-Fe) alloy were investigated. The samples were compressed with ratios from 10% to 80% at an interval of 10%. Based on the standing wave method, sound absorption coefficients of compressed samples with different thicknesses were obtained. It could be found that with the same compression ratio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…Meanwhile, when the frequency range was 100-2000 Hz, the absolute value and relative percentage of improvement of the theoretical average sound absorption coefficient fell from 0.3690 and 247.76% to 0.1050 and 15.44% respectively with thickness of the polyurethane foam increased from 10 mm to 40 mm. The major reason for this phenomenon was that sound absorption performance of the polyurethane foam in the entire frequency range was raised when its thickness rose, which was consistent with normal absorption property of the porous material [15][16][17]31,33,35]. Comparisons of theoretical data, simulation data, and experimental data of the sound absorption coefficients of the composite sound-absorbing structure are shown in Figures 9 and 10 respectively.…”
Section: Optimal Structural Parametersmentioning
confidence: 66%
See 4 more Smart Citations
“…Meanwhile, when the frequency range was 100-2000 Hz, the absolute value and relative percentage of improvement of the theoretical average sound absorption coefficient fell from 0.3690 and 247.76% to 0.1050 and 15.44% respectively with thickness of the polyurethane foam increased from 10 mm to 40 mm. The major reason for this phenomenon was that sound absorption performance of the polyurethane foam in the entire frequency range was raised when its thickness rose, which was consistent with normal absorption property of the porous material [15][16][17]31,33,35]. Comparisons of theoretical data, simulation data, and experimental data of the sound absorption coefficients of the composite sound-absorbing structure are shown in Figures 9 and 10 respectively.…”
Section: Optimal Structural Parametersmentioning
confidence: 66%
“…Judging from theoretical sound absorption mechanism of the microperforated panel absorber [18][19][20], it could be found that its sound absorption performance was determined by its geometric parameters and had little to do with its physical or chemical parameters. Owing to the investigated frequency ranges of 100-1000 Hz and 100-2000 Hz, the diameter of the prepared composite structures was 96 mm, which satisfied the requirement of the utilized AWA6128A detector for standing wave tube measurement of the sound absorption coefficients [33,35]. Through replacing the detected polyurethane foam by the prepared composite structure in Figure 4, actual sound absorption coefficients of the composite sound-absorbing structures were tested, which could provide experimental validation of the identification and optimization results.…”
Section: Actual Sound Absorption Coefficients Of the Composite Sound mentioning
confidence: 67%
See 3 more Smart Citations